2019
DOI: 10.2196/15218
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologists’ Adherence to the Latest Recommendations for Screening of Hydroxychloroquine Retinopathy in Saudi Arabia: Cross-Sectional Study

Abstract: Background Hydroxychloroquine (HCQ) has been used to manage many inflammatory skin conditions. Nevertheless, retinopathy continues to be its most significant adverse effect. The American Academy of Ophthalmology (AAO) recommends baseline ophthalmologic screening in the first year of HCQ treatment. However, a recent study found an inadequate awareness of the recommendations. Furthermore, limited data are available regarding the implementation of the recommendations among dermatologists. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In 2019, the adherence of Saudi Arabian dermatologists to HCQ screening recommendations for retinopathy was investigated among 76 dermatologists. Based on this research, it was found that the current standard of care for HCQ toxicity screening is lacking in several ways, including the use of the right diagnostic tests, the right amount of time between follow-ups, the prompt withdrawal of medications, and the identification of the causative agents [10]. Despite the limitations of this research regarding the sample size, no further studies were done in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 95%
“…In 2019, the adherence of Saudi Arabian dermatologists to HCQ screening recommendations for retinopathy was investigated among 76 dermatologists. Based on this research, it was found that the current standard of care for HCQ toxicity screening is lacking in several ways, including the use of the right diagnostic tests, the right amount of time between follow-ups, the prompt withdrawal of medications, and the identification of the causative agents [10]. Despite the limitations of this research regarding the sample size, no further studies were done in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, early/moderate cases oftentimes will remain stable after drug discontinuation, while severe cases may continue to advance for up to 20 years 85–88. Unfortunately, screening regimens and dosing practices remain insufficient and inconsistent despite published guidelines, emphasizing the importance of ophthalmologists and retina specialists in patient education 89–95…”
Section: Retinal/rpe Relatedmentioning
confidence: 99%
“…[85][86][87][88] Unfortunately, screening regimens and dosing practices remain insufficient and inconsistent despite published guidelines, emphasizing the importance of ophthalmologists and retina specialists in patient education. [89][90][91][92][93][94][95]…”
Section: Managementmentioning
confidence: 99%
“…In 2016, the American Academy of Ophthalmology published a statement on screening for antimalarial-induced retinopathy, authored by ophthalmologists, and the American College of Rheumatology posted a position statement on dosing of antimalarials and screening for retinopathy, authored by rheumatologists . The lack of interdisciplinary guidelines and prior studies showing nonadherence to single-specialty guidelines by dermatologists, rheumatologists, and opthalmologists highlight the important need for close collaboration between prescribing clinicians and ECSs to ensure the maximum therapeutic benefits of antimalarials while safeguarding vision. Recognizing this need, a multispecialty group of rheumatologists, ophthalmologists, and dermatologists authored a joint statement on the use of hydroxychloroquine and retinal screening and to stress the need for collaborative management .…”
Section: Introductionmentioning
confidence: 99%
“…4. Eye care specialists should recognize of the medical value of hydroxychloroquine, avoiding drug cessation in cases of uncertain or borderline findings.…”
mentioning
confidence: 99%